Surgical Treatment of Cardiac Tumors Combined with Coronary Pathology - Rostyslav M. Vitovskyi; Oleksandr V. Kupchynskyi; Ihor V. Martyshchenko; Maryna M. Serdiuk; Volodymyr O. Kupchinsky; Volodymyr V. Isaienko (Ukrainian Journal of Cardiovascular Surgery, 2022)
Introduction. Cardiac tumors (CT) occur in 0.3-0.7% of general population according to autopsies. The combination of CT with coronary artery disease (CAD) significantly complicates the clinical course of the disease.The aim. To study the frequency, features of the course and surgical treatment of patients with CT combined with CAD.Materials and methods. In the period from 01.01.1969 to 31.12.2020, surgical treatment of 976 patients with CT was performed at the National Amosov Institute of Cardiovascular Surgery of the NAMS of Ukraine, and 41 (4.2%) of these patients had lesions of the coronary arteries. In 39 patients (95.1%), CT were represented by benign tumors (myxomas), in 2 (2.4%) by malignant, poorly differentiated sarcoma and immature teratoma. For the correction of the pathology of coronary vessels, a whole range of surgical methods was used: stenting of left anterior descending artery (LAD), which was performed immediately before surgery to remove CT, in 3 patients (7.3%); coronary artery bypass grafting in 35 patients (85.4%); in cases of the presence of a muscular bridge that narrowed the LAD, dissection of this structure was performed in 2 patients (4.9%); left ventricular aneurysm repair surgery in 1 patient (2.4%). In 7 patients (17.1%), the operation was performed on urgent indications.Results. The average number of grafted arteries was 1.9 ± 0.3 (1 to 4) per patient. There were no mortality. Of the 41 patients with coronary artery lesions with CT, there were 2 cases of acute CAD as a result of their embolism by tumor fragments. Clinical manifestations in these patients differed significantly.Conclusions. Occurrence of coronary artery embolism in patients with CT according to our data is 0.2% of all patients with CT. CAD accompanies tumor lesions in 4.1% of cases and is diagnosed by angiography and computed tomography. To correct the lesion of the coronary arteries in CT, the full range of surgical techniques is used, including stenting of the coronary artery (spacecraft), coronary artery bypass grafting, removal of the myocardial bridge.